Identifying the Economic Potential of Indian Districts - Roberts, Mark (World Bank, Washington, DC, 2016)
Despite its rapid growth in recent decades, GDP per capita in India remains at a relatively low level by international standards, and the country continues to be marked by large subnational disparities in levels of well-being. These large disparities naturally lead to interest in India’s spatial landscape of potential for economic development. Against this backdrop, this paper presents the results of an analysis of underlying variations in economic potential across Indian districts, where economic potential is defined as the extent to which a district possesses factors that are important determinants of the ability to experience a high level of productivity. The analysis is based on a simple composite Economic Potential Index, which is constructed from variables for which robust evidence exists of their importance as determinants of local productivity. From the analysis, a picture emerges of a heterogeneous landscape of economic potential characterized by strong geographic clustering of districts. The paper also reveals particularly high levels of underperformance, relative to potential, for districts in Uttar Pradesh.